2016
DOI: 10.1007/s12178-016-9357-4
|View full text |Cite
|
Sign up to set email alerts
|

Complications of surgical intervention in adult lumbar scoliosis

Abstract: If nonoperative measures are unsuccessful in managing the pain and disability of adult spinal deformities, surgical correction may provide the potential for significant improvement in a patient's quality of life. However, these procedures have a relatively high risk of complications. Identifying patients that may benefit from surgical intervention requires a thorough understanding of potential complications and managing the risks of any individual patient. Complications do not necessarily result in poor outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…Complications were classified as major or minor similar to other studies in ASD. 11,12 A complication was classified as major if it prolonged hospitalization, required reoperation or an invasive intervention, caused prolonged or permanent morbidity, or resulted in death. For example, proximal junctional kyphosis requiring revision surgery was classified as a major complication, while proximal junctional kyphosis not requiring surgery was classified as a minor complication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complications were classified as major or minor similar to other studies in ASD. 11,12 A complication was classified as major if it prolonged hospitalization, required reoperation or an invasive intervention, caused prolonged or permanent morbidity, or resulted in death. For example, proximal junctional kyphosis requiring revision surgery was classified as a major complication, while proximal junctional kyphosis not requiring surgery was classified as a minor complication.…”
Section: Methodsmentioning
confidence: 99%
“…For example, proximal junctional kyphosis requiring revision surgery was classified as a major complication, while proximal junctional kyphosis not requiring surgery was classified as a minor complication. The list of minor and major complications was similar to a consensus list prepared by ASD surgeons and presented by Christiansen et al 11 Health-related quality-of-life (HRQOL) data collected at baseline, 6 weeks, and 2 years were analyzed; this included the Oswestry Disability Index (ODI), 36-item Short-Form Health Survey (SF-36; Physical Component Score and Mental Component Score), and the Scoliosis Research Society–22 questionnaire (SRS, subdomains: activity, pain, satisfaction, mental, appearance, and total).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of comorbidities, like the age, was once perceived as a restrictive factor for surgical intervention. However, this does not necessarily result in poor outcomes in recent literature, and favorable outcomes are not without complications (12,74) . Somehow, higher risk subjects potentially have more to gain, even if they encounter complications (12,50,61) .…”
Section: Comorbiditiesmentioning
confidence: 97%
“…On the other hand, there is the option of "surgical treatment" with up to 80% (9.52%-81.52%) complication rates and more than 50% re-operation rate, reported in several papers (8,9,63,68) . Teles et al (62) reported postoperative radiological (7 main categories) and instrumentrelated (7 main categories) complications and Christiansen et al (12) modified their work and stated 46 major and 41 minor complications under 10 main categories (infection, implantrelated, neurological, cardiopulmonary, gastrointestinal, radiographic, renal, wound problems, operative, and vascular). Surgery may be considered if patients have inadequate improvement with nonoperative measures.…”
Section: Conservative Treatmentmentioning
confidence: 99%
See 1 more Smart Citation